TEKNIK KONSELING “ KURSI KOSONG ” UNTUK MENGURANGI TINGKAT STRES PERKULIAHAN YANG MEMICU PENYALAHGUNAAN NARKOBA - Ayu Jingga Arisa; Nurina Dzawata Samcha; Choiril Ibadiyah Fikri; Noor Avia Ratnawati; Wiryo Nuryono; Devi Ratnasari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The